BIMBINGAN BELAJAR DAN KARIR BERBASIS KEARIFAN LOKAL DAN NILAI KELUARGA - I MADE OLAS ASTAWA (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
The strength of a nation depends on the strength of its education system, as has been demonstrated in several countries in Eastern Europe, Russia, China, India, and Latin America. One element of education that have strategic relevance is career guidance and counseling services in education, both formal, nonformal or informal. Career guidance services are developed conceptual and systemic will support the implementation of a strong educational system and capable of producing human resources which in turn will become a skilled work force and productive. Career development can contribute to the quality of employment and economic growth, particularly in terms of: (1) efficient use of funds in education and training to improve the achievement of the program, (2) the efficiency of the labor market with increased placements and ritensi work and reduce the waiting period and unemployment , (3) lifelong learning, workforce development, sustainability, employment by increasing participation in education and training, (4) the achievement of social goals, with increased activities in all elements of the population in education, training, and employment, (5) social justice, to help individuals and groups in overcoming obstacles in gender, ethnicity, age, disability, social class, institutional learning and work.